Perceptions by smallholder farmers of forest plantations in Malaysia - Ratnasingam, Jegatheswaran; Loras, Florin; Farrokhpayam, Saeid Reza; Mariapan, Manohar; Ab Latib, Hazirah; Liew, Kang Chiang (MDPI AG, 2021)
Plantation forests are perceived to be the supplementary source of wood material for the large wood products industry in Malaysia, amidst the steadily reducing supply from her natural forests. Despite the government’s initiated plantation forests scheme, the participation of smallholder farmers has been limited. Smallholder farmers constitute the largest proportion of private farmers involved in all sectors of agricultural and plantation tree crop cultivation, including commodities such as rubber and palm oil. Therefore, this study examines the lack of interest among smallholder farmers to participate in establishing forest plantations, although they have a strong presence in the palm oil and rubber sectors. A structured questionnaire survey was conducted among 12,895 smallholder farmers currently involved in palm oil, rubber and other tree-crop cultivation. The study found that this group has little knowledge and awareness of the forest plantation scheme available, and there is a prevailing perception that the establishment of forest plantations is not environment-friendly and leads to biodiversity loss. The poor economic return, small land holding, and poorly structured market and supply chain are perceived as the significant constraints faced that limit the interest among the target groups to participate in this sector. Any effort to reverse this trend and garner higher interest from the target group will necessarily require a new policy framework that boosts the economic outlook of forest plantations among smallholder farmers.